Wizualizacja w kształceniu nauczycieli - Dylak, Stanisław (Wydawnictwo Naukowe UAM, 1995)
In the book an attempt at describing theoretical bases and application of iconic representations in teacher education has been undertaken. The author has been directed by a need of practical reorientation of teacher education towards increasing number of these situations in which a student participates actively in creating his or her pedagogical knowledge through intellectual operations in reality. The author was inspired by such organization of educational process in which teacher candidate has a possibility to get to know himself or herself as an author of professional activities and he or she has an opportunity to practise initially in “safe” conditions. These assumptions have directed the author’s attention towards bringing closer pedagogical reality to students by its visualisations i.e. by means of iconic representations. An attractive and relevant vehicle for these representations is video technology. On the basis of theoretical analysis referred to a process of perception and visual memory, the educational usefulness of an iconic representation in teacher education has been confirmed. The author particularly adduced Obuchowski’s hypothesis about creative codes as support for his approach using visualisation in teacher education. It has been acknowledged that Obuchowki’s theory has helped to explain the role of visual representations in activating the previous structure of knowledge (common-sense knowledge), especially of those anchored in creative codes. This role consists in direct communication between iconic representations and those structures of knowledge which have been already recorded in learners’ minds in creative codes. This activating of the structures recorded in learners’ minds in creative codes, allows to name those structures, to order them and to reflect on them critically as well. The process of activating the learners’ previous structures allows the learners to refer those activated structures to the oncoming information. The assumptions justifying the use of the iconic representations are linked with the iconic dimensions pedagogical reality can be described on. Therefore this relation supports very strongly the use of visual-iconic code to help students to understand pedagogical reality. Four main functions were verified which iconic representations perform in teacher education, i.e. inspiration, self-confrontation, demonstration (presentation), and simulation. A trigger video plays very important role as an inspiring instrument. It has been empirically approved that the trigger video can be found as an instrument for searching and analysing teacher candidates’ pedagogical attitudes and skills. First of all those representations (there are very short and emotionally activating videos) facilitate verbalising students’ personal pedagogical theories (previous pedagogical knowledge they already have they start to be teacher candidates). Placing an observer in a situation with the task to be resolved presented on a video and demanding his or her immediate reaction, promotes discovering individual pedagogical preferences according to the event observed on the video. Observers are used to react spontaneously and consistently with their previous personal knowledge and experience. Under several conditions the trigger video may be successful in searching previous subject’s pedagogical experience. The research confirmed that that power of a given representation (i.e. video) to discriminate subjects’ reactions according to previous different experience is subjectively conditioned. It means that the representation should create a dilemma to the subject (observer) to assess what he or she sees on the film or what to do in referring to actions on that film. If the content, task or problem is far from subject’s level of experience, she or he can not see any point to start to act from.
Keywords: funkcje szkoły; wizualizacja; kształcenie nauczycieli; wiedza pedagogiczna; wideodrama; wiedza potoczna; symulacja; multimedia